Mid-Century Modern Design as a Cinematic Vision of Dystopia Based on Selected Examples of the 21st-Century Films and TV Series - Anna Wiśnicka (Załącznik Kulturoznawczy)
The text aims to investigate various uses of the mid-century modern period pieces in the production design of films and TV series developed after the year 2000 and presenting various visions of a dystopic future. The choice of time frame for the analysis was motivated by the desire to showcase the connotations between the mid-century modern and 21st-century visions of the future which can be broadly described as retrofuturistic. On account of its primary focus on progressive ideas, new materials and forms, mid-century modern has always been broadly associated with the design of the future. The author discusses various takes on set design to highlight a wide spectrum of narrations regarding the future and its cultural dimension in selected productions incorporating iconic mid-century design pieces and, more importantly, the non-verbal message they carry.